2018
DOI: 10.12659/msm.908840
|View full text |Cite
|
Sign up to set email alerts
|

Differential and Predictive Value of Galectin-3 and Soluble Suppression of Tumorigenicity-2 (sST2) in Heart Failure with Preserved Ejection Fraction

Abstract: BackgroundGalectin-3 and soluble suppression of tumorigenicity-2 (sST2) are promising biomarkers of cardiac fibrosis and ventricular remodeling. The purpose of this study was to investigate the diagnostic and predictive value of galectin-3 and sST2 for use in patients who have heart failure with preserved ejection fraction (HFpEF).Material/MethodsA total of 217 hospitalized patients with HF and 30 controls from a physical examination center were included. Venous blood was collected for the detection of circula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 26 publications
(25 reference statements)
1
35
0
2
Order By: Relevance
“…Twenty-eight were performed in Europe [ 20 , 32 36 , 38 , 40 , 41 , 43 45 , 50 , 52 , 53 , 55 – 57 , 59 , 63 , 64 , 66 , 69 , 73 , 76 78 ], 11 in North America [ 22 , 37 , 39 , 46 , 49 , 54 , 65 , 70 , 72 , 74 , 75 ], 11 in Asia [ 31 , 42 , 47 , 51 , 58 , 60 62 , 67 , 68 , 71 ] and one was a multi-country study [ 48 ]. The control populations were either healthy controls ( N = 14) [ 31 , 35 , 59 , 60 , 62 , 65 , 67 69 , 71 , 72 , 75 – 77 ] or were recruited at the same department as the patient population, but without DD or HFpEF ( N = 37) [ 32 34 , 36 42 , 58 , 61 , 63 , 64 , 66 , 70 ]. The mean age of the DD and HFpEF populations ranged from 51 to 74 years and...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty-eight were performed in Europe [ 20 , 32 36 , 38 , 40 , 41 , 43 45 , 50 , 52 , 53 , 55 – 57 , 59 , 63 , 64 , 66 , 69 , 73 , 76 78 ], 11 in North America [ 22 , 37 , 39 , 46 , 49 , 54 , 65 , 70 , 72 , 74 , 75 ], 11 in Asia [ 31 , 42 , 47 , 51 , 58 , 60 62 , 67 , 68 , 71 ] and one was a multi-country study [ 48 ]. The control populations were either healthy controls ( N = 14) [ 31 , 35 , 59 , 60 , 62 , 65 , 67 69 , 71 , 72 , 75 – 77 ] or were recruited at the same department as the patient population, but without DD or HFpEF ( N = 37) [ 32 34 , 36 42 , 58 , 61 , 63 , 64 , 66 , 70 ]. The mean age of the DD and HFpEF populations ranged from 51 to 74 years and...…”
Section: Resultsmentioning
confidence: 99%
“…Five DD studies included patients with HFpEF [ 38 , 43 , 48 , 73 , 76 ], one DD study included patients with signs and symptoms [ 44 ], but did not exclude on LVEF, and eight DD studies only included patients with LVEF above 45 or 50% [ 18 , 20 , 45 , 47 , 50 , 52 , 53 , 77 ]. The reference diagnoses used in the included studies varied from use of maximal velocity of the E-wave (e’) ( N = 10) [ 43 45 , 49 , 50 , 52 , 54 , 56 , 57 , 74 ] versus no tissue Doppler (TDI) measures ( N = 14) [ 18 , 20 , 22 , 38 , 46 48 , 51 , 53 , 55 , 73 , 76 78 ] for DD studies and, use of extensive criteria ( N = 13) [ 31 , 32 , 34 , 35 , 38 , 41 , 59 , 61 , 63 , 64 , 66 , 69 , 72 ], signs and symptoms of HF in combination with LVEF ( N = 11) [ 36 , 40 , 42 , 58 , 60 , 62 , 65 , 67 , 68 , 70 , 71 ], expert opinion ( N = 1) [ 33 ] or catheterization ( N = 3) [ …”
Section: Resultsmentioning
confidence: 99%
“…Recently, Gal-3 has been indicated to be involved in the following broad pathological processes: Inflammation [9], fibrosis, cell-to-cell [10,11] or cell-to-matrix [12] contacts, cell proliferation [13,14], and protection from apoptosis [15,16]. Furthermore, many studies have revealed that Gal-3 expression is detected in many disease conditions, such as heart disease [17][18][19][20][21][22][23], kidney disease [24][25][26][27], diabetes mellitus [24,25,28], viral infection [29][30][31][32], autoimmune disease [33][34][35][36], neurodegenerative disorders [37][38][39][40][41][42], and tumor formation [43][44][45][46][47][48][49][50][51][52].…”
Section: Clinical Significance and Applications Of Galectine-3 (Gal-3)mentioning
confidence: 99%
“…In the pathogenesis of AS, the proliferation of vascular smooth muscle cells (VSMCs) is the typical high-probability event accompanied by the generation of collagen fibers and the accumulation of lipids 5 . During the vasculopathy, the aberrant proliferation and migration of VSMCs from tunica media into the subendothelial layer triggers the vascular remodeling 6 . Besides, VSMCs are exposed to complex and diverse microenvironments, in return leading to the mutability of VSMCs.…”
Section: Introductionmentioning
confidence: 99%